Step in the Diagnosis and Treatment of Ovarian Cysts in Indonesian Primary Healthcare Facilities - Winata, I Gde Sastra; Louisa, Jennifer; Wibisana, I Dewa Nyoman Adi Ningrat; Sengga, Agnes Simona (British Journal of Healthcare and Medical Research, 2024)
Ovarian cysts are fluid-filled structures that form in or on the ovaries. In Indonesia (2015), there were 23,400 cases of ovarian cysts, with a death toll of 13,900 people. The difficulty of early detection causes most patients to be diagnosed at an advanced stage. This underlines the importance of its identification, especially in primary healthcare facilities as the frontline of the healthcare system. This article discusses the diagnosis and initial treatment of ovarian cysts in primary healthcare facilities in Indonesia.This article is a literature review composed through scientific paper and journal searching using the appropriate keywords. The inclusion criterias are journal articles, book chapters, or official reports from verified and recognized national or international organizations in English or Bahasa Indonesia. Through literature research, it was found that a comprehensive history, physical examination, and supporting investigations are required to diagnose ovarian cyst. Examination should include vital signs, lymph node assessment, chest and abdominal examination, gynecological investigation (speculum, vaginal touche), and retrovaginal examination. The imaging modality of choice for ovarian cysts is transvaginal ultrasonography (USG). In primary care settings, transabdominal ultrasound may be used as an alternative. In primary care settings, management of ovarian cysts is limited to recognizing and suspecting ovarian cysts. In cases suspected to be benign, observation of the development of the cyst is required. Once an ovarian cyst is suspected to be malignant, a referral is required.